Long‐term effects of maternal separation on the responsiveness of the circadian system to melatonin in the diurnal nonhuman primate (Macaca mulatta). Issue 3 (19th February 2014) - Rawashdeh, Oliver; Dubocovich, Margarita L.
Abstract Depression is often linked to early‐life adversity and circadian disturbances. Here, we assessed the long‐term impact of early‐life adversity, particularly preweaning mother–infant separation, on the circadian system's responsiveness to a time giver or synchronizer (Zeitgeber). Mother‐reared (MR) and peer‐reared (PR) rhesus monkeys were subjected to chronic jet‐lag, a forced desynchrony protocol of 22 hr T‐cycles [11:11 hr light:dark (LD) cycles] to destabilize the central circadian organization. MR and PR monkeys subjected to the T‐cycles showed split locomotor activity rhythms with periods of ~22 hr (entrained) and ~24 hr (free‐running), simultaneously. Continuous melatonin treatment in the drinking water (20 μg/mL) gradually increased the amplitude of the entrained rhythm at the expense of the free‐running rhythm, reaching complete entrainment by 1 wk. Upon release into constant dim light, a rearing effect on anticipation for both the predicted light onset and food presentation was observed. In MR monkeys, melatonin did not affect the amplitude of anticipatory behavior. Interestingly, however, PR macaques showed light onset and food anticipatory activities in response to melatonin treatment. These results demonstrate for the first time a rearing‐dependent effect of maternal separation in macaques, imprinting long‐term plastic changes on the circadian system well into late adulthood. These effects could be counteracted by the synchronizer molecule melatonin. We conclude that the melatonergic system is targeted by early‐life adversity of maternal separation and that melatonin supplementation ameliorates the negative impact of stress on the circadian system.